Baseline distribution and sources of selected agricultural runoff in the bottom water of an active cockle farming area, Bagan Pasir, Perak, Malaysia. (June 2021) - Joni, Amirul Azuan Md; Mohamat-Yusuff, Ferdius; Noor, Nurhanin Aqila Mohammed; Mohamed, Khairul Nizam; Ash'aari, Zulfa Hanan; Kusin, Faradiella Mohd; Zulkeflee, Zufarzaana; Zulkifli, Syaizwan Zahmir; Ismail, Ahmad; Arshad, Aziz
Abstract: This paper aims to study the spatial and temporal patterns of selected agricultural runoff, specifically in terms of glyphosate, nitrate, and ammonia in bottom water, as well as their possible sources, within an active cockle farming area in Bagan Pasir, Perak, Malaysia. Samples were taken along the cockle farming area from March to November 2019. Glyphosate was analyzed using HPLC with both extraction and derivatization methods using 9-fluorenyl-methyl chloroformate (FMOC-Cl), while nitrate and ammonia levels were determined using the standard Hach method. Generally, glyphosate, nitrate, and ammonia were present within the study site with the average concentration of 37.44 ± 12.27 μg/l, 1.65 ± 0.52 mg/l, and 0.37 ± 0.19 mg/l, respectively. The results suggest that glyphosate and nitrate might be derived from an inland source, while a uniform and low level of ammonia suggested might originate from lithogenic origins. Continuous monitoring remains encouraged. Graphical abstract: Unlabelled Image Highlights: High trend of glyphosate and nitrate concentration signify these compounds derived from the nearby anthropogenic source. Concentration of glyphosate, nitrate, and ammonia varied according to the rainfall precipitation Significant increase of compound during high rainfall precipitation indicates that inland source play a major role within the study area. PCA outputs indicate compound contributions related to pollution sources, either runoff or from inland sewage.